Penerapan Aplikasi Mobile E-Card Employee Menggunakan Ionic Framework (Studi Kasus : PT. Darma Henwa, Tbk- Acp) - Bidah; Noor Islami, Raisa (Journal Information Technology Trends (JITRENDS), 2024)
PT. Darma Henwa, Tbk-ACP is a mining contractor company with various departments, including the Management Information System (MIS). Employee ID card data collection and verification are currently manual using Microsoft Excel, causing data to be disorganized and difficult to access. This research develops the "E-Card Employee" application for Android using the prototyping method and the Ionic Framework, with data modeling through ERD and DFD. The results show that this application facilitates employee data management, increases efficiency, and provides a digital solution for ID cards that can be used if the physical ID card is lost or left behind.